When Is Genocide a Crime of Genocide? The Holodomor and the Katyn Massacre as a Crime of Genocide - Masło, Krzysztof (Review of European and Comparative Law, 2023)
The Holodomor and Katyn Massacre are founding crimes of the USSR and the Eastern Bloc’s state. Their common feature was an attempt to annihilate nations and prevent them from achieving independence. Quite often, both crimes are called genocide, but their legal qualification from the perspective of the then international law is extremely difficult. However, there are solid grounds for qualifying both of these crimes, and particularly the Katyn Massacre, as genocide. As a result of the development of the law of armed conflicts in international law in the 1930s and 1940s, there was a ban on committing acts that the 1948 Convention defined as genocide.